Mesohepatectomy for Centrally Located Tumors in Children - Amesty, Maria Virginia; Chocarro, Gloria; Sánchez, Alejandra Vilanova; Cerezo, Vanesa Nuñez; de la Torre, C. A.; Encinas, Jose Luis; Arance, Manuel Gamez; Hernández, Francisco; Santamaria, Manuel Lopez (European Journal of Pediatric Surgery, 2016)
Introduction Central hepatectomy or mesohepatectomy (MH) is a complex surgical technique rarely used in children. It is indicated in central tumors to preserve functioning liver mass avoiding an extended right hepatectomy. The purpose of this article is to analyze our experience with this technique.Methods We reviewed five patients who underwent MH in the period from 2008 to 2014. Diagnoses were hepatoblastoma PRETEXT III (two cases), hepatic embryonal sarcoma (one case), focal nodular hyperplasia (one case), and vascular tumor with rapid growth in a newborn causing an acute liver failure, compartment syndrome, and multiple organ failure (one case). In all cases, the tumor was centrally located, including the segment IVb, with large displacement of the hepatic pedicle in two cases.Results MH was standard in three cases and under total vascular exclusion in two cases. All children are alive with a mean follow-up of 38 (6–70) months. None of the children required reoperation because of bleeding. One child developed a biliary fistula in the cutting area that closed spontaneously. The newborn with the vascular tumor required the placement of a Gore-Tex patch (W. L. Gore & Associates, Inc, Flagstaff, Arizona, United States) to relieve the compartment syndrome. He subsequently underwent partial embolization of the tumor and MH under vascular exclusion.Conclusions In selected patients, MH is an alternative to trisegmentectomy and should be available in advanced pediatric hepatobiliary units.
Keywords: mesohepatectomy; central hepatectomy; hepatic tumor in children